Features of cytokine profile in patients with sarcoidosis - N. M. Lazareva; O. P. Baranova; I. V. Kudryavtsev; N. A. Arsentieva; N. E. Liubimova; T. P. Ses’; M. M. Ilkovich; Areg A. Totolian (Медицинская иммунология, 2020)
Sarcoidosis is an inflammatory disease of unknown etiology with damage to the lungs and other organs characterized by development of necrosis-free epithelioid cell granulomas. Granulomatous inflammation characterized by the activation of different immune systems cells, in particular T lymphocytes, and the cytokines production. Our study was aimed at investigating the characteristics of the cytokine profile of blood plasma in patients with sarcoidosis. We studied peripheral blood plasma samples of patients with sarcoidosis (n = 52). The control blood samples were taken from healthy volunteers (n = 22). The level of 46 cytokines (pg/ml) was determined, as follows: IL-1α, IL-1β, IL-2, IL-3, IL-4, IL-5, IL- 6, IL-7, IL-9, IL-12 (p40), IL-12 (p70), IL-13, IL-15, IL-17A, IFNα2, IFNγ, TNFα, TNFβ, IL- 1ra, IL-10, EGF, FGF-2, Flt3 Ligand, G-CSF, GM-CSF, PDGF-AA, PDGF-AB / BB, TGFα, VEGF-A, sCD40L, CCL2, CCL3, CCL4, CCL5, CCL7, CCL11, CCL17, CCL20, CCL22, CXCL1, CXCL8, CXCL9, CXCL10, CXCL11, CXCL13, CX3CL1. Significantly higher levels of interleukins and some proinflammatory cytokines were found in the patients with sarcoidosis, i.e., IL-3, 0.70 vs 0.20, p = 0.003; IL-4, 14.37 vs 3.15, p = 0.009; IL-5, 1.06 vs 0.89, p < 0.001; IL-12 (p70), 1.27 vs 0.56, p = 0.028; IL-17A, 1.48 vs 0.43, p < 0.001; IFNα2, 41.79 vs 25.04, p = 0.003; IFNγ, 4.13 vs 1.14, p < 0.001; TNFα, 21.67 vs 6.70, p < 0.001; anti-inflammatory cytokine IL-10, 1.03 vs 0.45, p = 0.019; growth factors: FGF-2, 40.08 vs 30.58, p = 0.008, G-CSF, 24.18 vs 8.21, p = 0.006, and VEGF-A, 42.52 vs 26.76, p = 0.048; chemokines: CCL3, 3.86 vs 1.33, p < 0,001; CCL17, 78.24 vs 26.24, p < 0.001; CCL20, 7.19 vs 5.64, p = 0.021; CCL22, 660.60 vs 405.00, p < 0,001; CXCL9, 4013 vs 1142, p < 0,001; CXCL10, 565.90 vs 196.60, p < 0.001; CXCL11, 230.20 vs 121.10, p = 0.018; CX3CL1, 56.99 vs 5.16, p < 0.001. Peripheral blood chemokine CCL11 levels were significantly lower in patients compared to the group of healthy volunteers: 77.58 vs 124.70, p = 0.022. The features of the cytokine profile in patients with sarcoidosis may indicate their important role in the processes of formation and outcomes of granulomas. These issues require an additional detailed study, comparison with phenotypes, differential course and outcomes of the disease.